073 Headaches of raised intracranial pressure as a presenting feature of malignant infiltration in the cauda equina. (23rd August 2021) - Silsby, Matthew; Martin, Andrew; Varikatt, Winny; Vucic, Steve; Fung, Victor SC; Menon, Parvathi
Abstract : Introduction: Raised intracranial pressure (ICP) headache is rarely caused by spinal cord lesions. We present two patients with rare presentations of uncommon malignancies surrounding the cauda equina resulting in raised ICP headache. Cases: Patient 1, a 54-year-old man, presented with two months of headache, blurred vision and 9kg weight loss. Fundoscopy revealed papilloedema. Shortly after presentation he developed lower limb weakness with absent tendon reflexes. MRI brain was unremarkable. MRI spine showed diffuse nerve root thickening and effacement of the CSF spaces around the cauda equina. Patient 2, a 51-year-old man, presented with four months of headache and blurred vision, progressive lower limb weakness and 20kg weight loss over 12 months. MRI brain showed two small lesions insufficient to cause raised ICP. MRI spine showed extensive lower spinal cord infiltration with diffuse thickening of the cauda equina. Pathological assessments revealed malignant histiocytosis in patient 1 and primary leptomeningeal gliomatosis in patient 2. Discussion: These cases demonstrate the rare presentation of raised ICP headache resulting from spinal lesions. In both cases the original presentation with raised ICP headache and absent lower limb signs led to diagnostic delay. Malignant lesions in the spinal column can increase ICP, though the mechanism is debated. These cases emphasise the importance of a broader search for the aetiology of raised ICP headache in the absence of a causative lesion on primary brain imaging. Further, these cases highlight rare presentations of two uncommon pathological entities.